U-Pb geochronology of cassiterite and zircon from the Dulong Sn-Zn deposit: Evidence for Cretaceous large-scale granitic magmatism and mineralization events in southeastern Yunnan province, China - Liu, Y.; Li, Zheng-xiang; Li, H.; Guo, L.; Xu, W.; Ye, L.; Li, C.; Pi, D. (Science China Press, 2007)
The Dulong Sn-Zn deposit is one of the largest cassiterite-sulfide deposits in China. There are different opinions regarding the genesis of this deposit, partly due to the lack of reliable geochronological data. We report here results of the first attempt to determine the magmatic and mineralization ages of this deposit and related late-Yanshanian granites through U-Pb dating of cassiterite and zircon. Four cassiterite samples from the Manjiazhai section yields a means 206Pb/238U age of 79.8+/- 3.2Ma (MSWD = 3.16), and a 238U/204Pb-206Pb/204Pb isochronal age of 82.0 +/- 9.6Ma (MSWD = 4.81) using the TIMS U-Pb method. Zircon from a concealed granite at the Manjiazhai section yielded a means 206Pb/238U age of 92.9 +/- 1.9Ma (N = 10, MSWD = 0.71), and zircon derived from a granite-porphyry outcrop at the Tongjie section yielded a means 206Pb/238U age of 86.9 +/- 1.4Ma (N = 9, MSWD = 3.70), both obtained using the SHRIMP U-Pb method. These ages suggest that the tin (copper) mineralization in the Dulong Sn-Zn deposit was mainly related to the late Cretaceous magmatic hydrothermal events. The geochronological data of the Gejiu (Sn) and the Bainiuchang (Ag) super-large deposits and related Yanshanian granites indicate that there was a large-scale granitic magmatism and mineralization event during the Cretaceous in southeastern Yunnan, which might have been related to the lithospheric extension of the South China Block in late Mesozoic.